Sulfide solid electrolyte and preparation method and application thereof

Through the multi -element -mixed strategy, optimize the chemical properties of vulcanizes electrolytes, solve the problem of poor stability in the air environment, realize the high -chamber temperature ionic conductivity and good air stability, improve the safety performance and work of the battery Temperature range.

CN119381529AActive Publication Date: 2025-01-28TONGXIANG FRONTIER NEW MATERIALS RES INST +1

Patent Information

Application Number
CN202411500801.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The existing sulfide solid electrolytes have poor stability in air environments, making it difficult to achieve high room temperature ionic conductivity and good air stability at the same time.

Method used

Through the strategies mixed with multiple elements, use SN, GE, CU, BI, SB, ZR, CD, V, CR and other elements to replace some P elements, and replace some S elements through O element to adjust the proportion and halogen of the doped element and halogen. Content, optimize the chemical properties of vulcanizes electrolytes.

Benefits of technology

The electrolytes of vulcanization are stable under air conditions, maintaining high -chamber temperature ion conductivity and low activation energy, and improving the safety performance and working temperature range of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381529A_ABST
    Figure CN119381529A_ABST
Patent Text Reader

Abstract

The invention discloses a sulfide solid electrolyte Li < 6 + a + 5b-c-b > P < 1-a-b > Sn M S < 5-c-d > X < 1 + c > O < d >. Wherein M is one or more of Ge, Cu, Bi, Sb, Zr, Cd, V and Cr and is the average valence of M, X is one or more of F, Cl, Br and I, and a + blt is larger than or equal to 0.01 and smaller than or equal to 0.01; 0.1 < = c < = 0.75, 0.001 < = d < = 1; the preparation method comprises the following steps: dry-mixing the raw materials according to the stoichiometric ratio of the formula (I) in an inert protective atmosphere and under anhydrous and anaerobic conditions, then carrying out heat treatment at 400-600 DEG C for 3-30 hours, and finally cooling to obtain the sulfide electrolyte, the invention also discloses application of the sulfide solid electrolyte in the aspect of an all-solid-state battery. The sulfide solid electrolyte with the argyrodite crystal structure can be stably stored under the air condition without any coating layer or additive protection, and meanwhile, the high-room-temperature ionic conductivity and low activation energy of the sulfide solid electrolyte are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials, and specifically relates to a sulfide solid electrolyte and a preparation method and application thereof. Background Art

[0002] Since the first commercial lithium-ion battery was launched in 1991, lithium-ion batteries have been widely used in various electronic devices due to their high energy density, good cycle performance and rate performance. However, most commercial lithium-ion batteries currently use organic liquid electrolytes, which have a series of safety issues such as electrolyte leakage and lithium dendrite growth piercing the diaphragm, which in turn causes short circuits or even explosions, limiting the development and progress of lithium-ion batteries.

[0003] Solid-state batteries use inorganic solid electrolytes with good thermal stability, which reduces the risk of battery fire and explosion, and effectively improves the safety performance and operating temperature range of the battery. Among the many types of solid electrolytes, sulfide electrolytes have high room temperature ionic conductivity closest to liquid electrolytes and are expected to replace liquid electrolytes. However, they have poor air stability and are easily reacted with water and oxygen in the air, resulting in battery performance degradation.

[0004] There are currently two main solutions to the problem of poor air stability of sulfide electrolytes. One is to improve it by introducing additives and surface protective layers (CN106887638A), and the other is to introduce elements such as O or N into sulfide electrolytes (CN109970083A, CN111430808A), so as to achieve batch use in air environment / dry room. However, no matter which method is used, the work reported so far is difficult to achieve good air stability and high room temperature ionic conductivity at the same time.

[0005] Based on the above, it is necessary to provide a sulfide solid electrolyte with excellent chemical stability and high room temperature ionic conductivity, in order to promote the actual commercial application of all-solid-state batteries. Summary of the invention

[0006] Based on the theory of hard and soft acids and bases, the currently reported strategy of doping soft acid metal elements or non-metallic elements such as O, N, and Se can effectively improve the air stability of the electrolyte, but it usually comes at the expense of reducing the room temperature ionic conductivity of the electrolyte or increasing its activation energy (Chinese patent CN108493479A). The present invention provides a novel multi-element substitution method for simultaneously improving the air stability and room temperature ionic conductivity of sulfide electrolytes. The sulfide solid electrolyte with a argyrodite crystal structure obtained by the method can be stably stored in air conditions without any coating layer or additive protection.

[0007] One of the purposes of the present invention is to provide a multi-element co-doped argyrodite-type sulfide electrolyte, by optimizing the doping amount and doping ratio of each element, regulating the chemical properties of the material, thereby improving the air stability of the electrolyte material. And by increasing the configuration entropy of the system through the strategy of multi-element co-doping, while improving the air stability of the sulfide electrolyte, it ensures its high room temperature ionic conductivity and low activation energy.

[0008] Specifically, by simultaneously using multiple elements of Sn, Ge, Cu, Bi, Sb, Zr, Cd, V, and Cr to replace part of the P element, and using the O element to replace part of the S element, and by adjusting the ratio between the doping amounts of the two doping elements and the halogen content, a sulfide solid electrolyte with higher air stability and room temperature ionic conductivity can be obtained.

[0009] Specifically, the present invention provides a sulfide solid electrolyte, as shown in formula (I): Li 6+a+5b-c-bɛ P 1-a-b Sn a M b S 5-c-d X 1+c O d (I); Wherein, M is one or more of Ge, Cu, Bi, Sb, Zr, Cd, V, and Cr, ɛ is the average valence of M, X is one or more of F, Cl, Br, and I, 0.01≤a+b<1, 0.1≤c≤0.75, and 0.001≤d≤1.

[0010] Furthermore, the three strong characteristic peaks in the XRD diffraction spectrum of the sulfide electrolyte are located at 25.5±0.5°, 30.1±0.5°, and 31.5±0.5°.

[0011] Furthermore, the size of the sulfide electrolyte particles is 200nm-5μm, and the room temperature ionic conductivity is (6.0-12.0) mS·cm -1 , the activation energy is (0.20-0.36) eV.

[0012] A second object of the present invention is to provide a method for preparing the above-mentioned multi-element doped sulfide solid electrolyte, comprising the following steps: Under a protective atmosphere (such as argon, nitrogen) and anhydrous and oxygen-free conditions, the raw materials are dry-mixed according to a certain stoichiometric ratio, then subjected to high-temperature heat treatment, and finally cooled to obtain a sulfide electrolyte.

[0013] As a preferred solution, the raw material compound of the doping element M is a sulfide or a halide, and the raw material compounds of the doping elements X and O are lithiates or doped metal compounds.

[0014] As a more preferred embodiment, the raw material compound of the doping element M is a sulfide, and the raw material compounds of the doping elements X and O are lithiates.

[0015] Specifically, the raw material compound of the doping element M is one or more of GeS2, Cu2S, Bi2S3, Sb2S5, ZrS2, CdS, V2S5, CrS3, the raw material compound of the doping element X is one or more of LiF, LiCl, LiBr, LiI, and the raw material compound of the doping element O is Li2O.

[0016] Furthermore, the rotation speed during dry mixing is 100-20000 rpm, preferably 10000-15000 rpm, and the dry mixing time is 3 minutes to 2 hours, preferably 5-10 minutes.

[0017] Furthermore, the heat treatment temperature is 400-600°C, preferably 480-550°C.

[0018] Furthermore, the heat treatment time is 3-30 hours, preferably 6-10 hours.

[0019] The present invention uses multiple metal elements to co-dope the P position and uses oxygen to replace part of the sulfur element, so that the prepared sulfide electrolyte has high room temperature ionic conductivity and good air stability, as well as low activation energy. The solid-state lithium-ion battery assembled based on the sulfide electrolyte has a high discharge specific capacity and good cycle stability.

[0020] A third object of the present invention is to provide application of the above-mentioned sulfide solid electrolyte in all-solid-state batteries.

[0021] Furthermore, the specific application process is as follows: the prepared sulfide electrolyte or a mixture thereof with a binder is pressed into a sheet, and then a positive electrode, a negative electrode and a current collector are prepared on the upper and lower surfaces of the obtained electrolyte sheet respectively.

[0022] Furthermore, the mass percentage content of the sulfide solid electrolyte in the mixture of the sulfide solid electrolyte and the binder is not less than 80%.

[0023] Furthermore, the binder is selected from at least one of polytetrafluoroethylene (PTFE) and polyamide (TPA).

[0024] Compared with the prior art, the present invention has the following beneficial effects: (1) We developed a multi-element co-doped oxygen-containing sulfide electrolyte that effectively improves air stability while ensuring high room-temperature ionic conductivity and low activation energy.

[0025] (2) By adjusting and optimizing the doping amount and doping ratio of various metal / oxygen elements with different valence states, the comprehensive improvement of various performances of the electrolyte is achieved.

[0026] (3) The entire process is relatively simple and does not involve high-pressure reaction conditions and expensive large-scale chemical equipment. It has the advantages of high output value and suitability for large-scale preparation. The various properties of the sulfide electrolyte and solid-state lithium-ion battery prepared according to the method of the present invention are significantly improved, which helps to accelerate the commercialization and application of all-solid-state lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The SEM photos of the solid electrolytes prepared in Examples 1-3 and Comparative Examples 1-3 are shown.

[0028] Figure 2 The XRD spectra of the solid electrolytes prepared in Examples 1-3 and Comparative Examples 1-3 are shown.

[0029] Figure 3 It is a comparison chart of air exposure time-hydrogen sulfide production of the solid electrolytes prepared in Examples 1-3 and Comparative Examples 1-3.

[0030] Figure 4 The AC impedance spectra of the solid electrolytes prepared in Examples 1-3 and Comparative Examples 1-3 are shown.

[0031] Figure 5 This is a comparison chart of the cycle performance of all-solid-state lithium batteries assembled using the solid electrolytes prepared in Example 3 and Comparative Example 1.

[0032] Figure 6 This is the battery cycle performance diagram of Application Example 1.

[0033] Figure 7 This is the battery cycle performance diagram of Application Example 2. DETAILED DESCRIPTION

[0034] The following examples further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention.

[0035] Example 1 Li 5.6 P 0.9 Sn 0.05 Ge 0.05 S 4.47 Cl 1.5 O 0.03 A method for preparing a sulfide electrolyte, the method comprising the following steps: (1) At 10000 rpm, Li2O, LiCl, Li2S, P2S5, SnS2, and GeS2 were dry-mixed at a molar ratio of 0.03:1.5:2.02:0.45:0.05:0.05 for 3 minutes to obtain a mixture; (2) The mixture is heat treated at 500°C for 8 hours to obtain Li 5.6 P 0.9 Sn 0.05 Ge 0.05 S 4.47 Cl 1. 5O 0.03 Sulfide electrolytes.

[0036] Example 2 Li 5.6 P 0.9 Sn 0.04 Bi 0.03 Sb 0.03 S 4.46 Cl 1.5 O 0.04 A method for preparing a sulfide electrolyte, the method comprising the following steps: (1) At 10000 rpm, Li2O, LiCl, Li2S, P2S5, SnS2, Bi2S3, and Sb2S5 were dry-mixed at a molar ratio of 0.04:1.5:2.01:0.45:0.04:0.015:0.015 for 3 minutes to obtain a mixture; (2) The mixture is heat treated at 500°C for 8 hours to obtain Li 5.6 P 0.9 Sn 0.04 Bi 0.03 Sb 0.03 S 4.4 6Cl 1.5 O 0.04 Sulfide electrolytes.

[0037] Example 3 Li 5.63 P 0.9 Sn 0.03 Ge 0.02 Cu 0.01 Bi 0.02 Sb 0.02 S 4.45 Cl 1.5 O 0.05 A method for preparing a sulfide electrolyte, the method comprising the following steps: (1) At 10000 rpm, Li2O, LiCl, Li2S, P2S5, SnS2, GeS2, Cu2S, Bi2S3, and Sb2S5 were dry-mixed at a molar ratio of 0.05: 1.5: 2.015: 0.45: 0.03: 0.02: 0.005: 0.01: 0.01 for 3 minutes to obtain a mixture; (2) The mixture is heat treated at 500°C for 8 hours to obtain Li 5.63 P 0.9 Sn 0.03 Ge 0.02 Cu 0.01 Bi 0.02 Sb 0.02 S 4.45 Cl 1.5 O 0.05 Sulfide electrolytes.

[0038] Comparative Example 1 Li 5.5 PS 4.5 Cl 1.5 A method for preparing a sulfide electrolyte, the method comprising the following steps: (1) dry-mixing LiCl, Li2S and P2S5 at a molar ratio of 1.5:2:0.5 at 10000 rpm for 3 minutes to obtain a mixture; (2) The mixture is heat treated at 500°C for 8 hours to obtain Li 5.5 PS 4.5 Cl 1.5 Sulfide electrolytes.

[0039] Comparative Example 2 Li 5.6 P 0.9 Sn 0.1 S 4.5 Cl 1.5 A method for preparing a sulfide electrolyte, the method comprising the following steps: (1) dry-mixing LiCl, Li2S, P2S5 and SnS2 at a molar ratio of 1.5:2.05:0.45:0.1 at 10000 rpm for 3 minutes to obtain a mixture; (2) The mixture is heat treated at 500°C for 8 hours to obtain Li 5.6 P 0.9 Sn 0.1 S 4.5 Cl 1.5 Sulfide electrolytes.

[0040] Comparative Example 3 Li 5.6 P 0.9 Sn 0.1 S 4.4 Cl 1.5 O 0.1 A method for preparing a sulfide electrolyte, the method comprising the following steps: (1) At 10000 rpm, dry-mix Li2O, LiCl, Li2S, P2S5, and SnS2 at a molar ratio of 0.1:1.5:1.95:0.45:0.1 for 3 minutes to obtain a mixture; (2) The mixture is heat treated at 500°C for 8 hours to obtain Li 5.6 P 0.9 Sn 0.1 S 4.4 Cl 1.5 O 0.1 Sulfide electrolytes.

[0041] In order to fully understand the structure and chemical properties of the sulfide electrolytes prepared in Examples 1-3 and Comparative Examples 1-3, samples were taken and tested, as follows: (1) Scanning electron microscope (SEM) test Figure 1 The SEM comparison photos of the solid electrolytes prepared in Examples 1-3 and Comparative Examples 1-3 are shown. As can be seen from the figure, the electrolyte particle size distribution of Example 1 is about 500nm to 6μm, the electrolyte particle size distribution of Example 2 is about 300nm to 5μm, the electrolyte particle size distribution of Example 3 is about 200nm to 3μm, the electrolyte particle size distribution of Comparative Example 1 is about 2μm to 10μm, the electrolyte particle size distribution of Comparative Example 2 is about 1μm to 6μm, and the electrolyte particle size distribution of Comparative Example 3 is about 1μm to 5μm, that is, the average size of the product of the embodiment is less than the average size of the product of the comparative example, which also determines that there is a certain difference in the performance of the all-solid-state battery assembled using the embodiment and the comparative example.

[0042] (2) X-ray diffraction (XRD) test Figure 2 The XRD spectra of the solid electrolytes prepared in Examples 1-3 and Comparative Examples 1-3. As can be seen from the figure, the sulfide electrolytes prepared in the Examples and Comparative Examples have a characteristic peak at 25.5±0.5°, 30.1±0.5°, and 31.5±0.5°, and there are no diffraction peaks of other raw materials, indicating that the prepared sulfide electrolyte samples are pure phases. The relative intensities of the diffraction peaks are somewhat different, but all satisfy (I1+I3) / I2=1.80±0.20.

[0043] (3) Air stability (H2S production under air exposure) test Figure 3 The air exposure time-hydrogen sulfide production comparison chart of the solid electrolytes prepared in Examples 1-3 and Comparative Examples 1-3. 100 mg of sulfide electrolyte powder was pressed into 10 mm particles at 150 MPa; the particles were heated at 40000 cm 3 The samples were exposed to humid nitrogen gas (40% relative humidity) containing water vapor for 30 minutes in a sealed container. The H2S gas generation or content was calculated from the H2S concentration measured by the H2S gas sensor.

[0044] (4) Temperature resistance test Samples were taken for variable temperature AC impedance spectroscopy test. The specific test process is as follows: 0.1g electrolyte powder sample was weighed and pressed into a sheet at 150MPa. Stainless steel was attached to the upper and lower surfaces of the obtained electrolyte sheet as a current collector. The electrolyte ceramic sheet was tested for AC impedance spectroscopy in the frequency range of 8MHz to 1Hz using an electrochemical workstation (ZAHNER, Zennium Pro) to obtain its impedance. Test conditions: The amplitude was 10mV, and data was collected every 10℃ in the temperature range of 10-60℃. The impedance data at 25℃ was used to calculate the room temperature ionic conductivity.

[0045] According to the results of the temperature-dependent impedance test, the ionic conductivity of each electrolyte sample at different temperatures was calculated, including the room temperature ionic conductivity. The calculation formula for ionic conductivity is: σ = L / RS , L is the thickness of the electrolyte sheet, R is the impedance of the electrolyte, and S is the contact area.

[0046] According to the ionic conductivity of each sample at different temperatures, the activation energy E of each electrolyte sample was calculated according to the following Arrhenius equation: a :

[0047] Where T is the absolute temperature, A is the pre-exponential factor, k B is the Boltzmann constant.

[0048] The AC impedance test results of each electrolyte sample prepared in Examples 1-3 and Comparative Examples 1-3 before and after exposure to air are as follows: Figure 4-5 As shown, the ionic conductivity retention rate and temperature-dependent impedance test results calculated thereby are shown in Table 1.

[0049] Table 1

[0050] Depend on Figure 4-5As can be seen from Table 1, the sulfide electrolyte doped with more elements exhibits better air stability, higher room temperature ionic conductivity and lower activation energy.

[0051] Application Example 1 Weigh 100 mg of the sulfide electrolyte powder prepared in Example 3 or Comparative Example 1, pour it into a PEEK mold with a diameter of 10 mm, and press it at 150 MPa to form an electrolyte layer. 0.9 Co 0.05 Mn 0.05 O2 (NCM90), sulfide electrolyte powder obtained in Example 3 or Comparative Example 1, and carbon nanotubes (CNT) are mixed, and the obtained mixture is manually ground for 1 hour to obtain a composite positive electrode powder. A certain amount of composite positive electrode powder is weighed and evenly spin-coated on one side of the sulfide electrolyte layer, and pressed at 50 MPa to obtain a composite positive electrode layer. On the other side of the electrolyte layer, a lithium sheet with a diameter of 4 mm and a thickness of 10 μm and an indium sheet with a diameter of 8 mm and a thickness of 50 μm are successively attached, and the negative electrode layer is obtained by pressing at 100 MPa. Finally, the assembled battery is placed in a Schweizerok battery mold as a whole and cold pressed at a pressure of 150 MPa, and stainless steel gaskets are added on both sides of the battery as current collectors, thereby completing the assembly of the all-solid-state battery.

[0052] At 1C rate and current density of 1.78 mA cm -2 、Active substance loading 8.65mg·cm -2 At 30°C, two groups of all-solid-state batteries were tested for charge and discharge cycles. The results are as follows Figure 6 During the test, the coulombic efficiency of the first cycle (0.1C) of the battery in Example 3 was greater than 75%, and 191 mAh·g -1 The specific capacity of the battery can still be higher than 160 mAh g after 100 cycles at 1C rate. -1 The specific capacity of the battery in the comparative example 1 is only 68% in the first cycle (0.1C). After 100 cycles at 1C rate, the specific capacity is increased from 130 mAh g -1 Down to 120mAh g -1 The following are the discharge specific capacity and cycle stability which are lower than those of the battery group in Example 3.

[0053] Application Example 2 A certain amount of the sulfide electrolyte powder prepared in Example 3 was weighed, mixed with polytetrafluoroethylene (PTFE) at a weight ratio of 98.5:1.5, and then hot-rolled to obtain Li 5.68 P 0.9 Sn 0.02 Ge 0.02 Cu 0.02Bi 0.02 Sb 0.02 S4Cl 1.5 O0 .5 -PTFE composite electrolyte film. The single crystal nickel-cobalt-manganese ternary positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 O2 (NCM90), the sulfide electrolyte powder obtained in Example 3, and carbon nanotubes (CNT) were mixed and manually ground for 1 hour to obtain a composite positive electrode powder. A certain amount of composite positive electrode powder was weighed and evenly spin-coated on one side of the composite electrolyte membrane, and pressed at 50 MPa to obtain a composite positive electrode layer. Subsequently, a lithium sheet with a diameter of 4 mm and a thickness of 10 μm and an indium sheet with a diameter of 8 mm and a thickness of 50 μm were successively attached to the other side of the composite electrolyte membrane, and pressed at 100 MPa to obtain a negative electrode layer. Finally, the assembled battery was placed under a pressure of 150 MPa for cold pressing for 3 minutes, and stainless steel gaskets were added on both sides of the battery as current collectors to complete the assembly of the all-solid-state battery.

[0054] At 1C rate and current density of 1.78 mA cm -2 、Active substance loading 8.65mg·cm -2 At 30°C, the all-solid-state battery was subjected to charge and discharge cycle tests. The results are as follows Figure 7 During the test, the battery's first cycle (0.1C) coulombic efficiency was greater than 80%, and after 50 cycles at 1C, it could release more than 100 mAh g -1 Specific capacity.

Claims

1. A sulfide solid electrolyte, characterized in that The composition is shown in formula (I): Li 6+a+5b-c-bɛ P 1-a-b Sn a M b S 5-c-d X 1+c O d , formula (I); Wherein, M is one or more of Ge, Cu, Bi, Sb, Zr, Cd, V, and Cr, ɛ is the average valence of M, X is one or more of F, Cl, Br, and I, 0.01≤a+b<1, 0.1≤c≤0.75, and 0.001≤d≤1.

2. The sulfide solid electrolyte according to claim 1, characterized in that The three strong characteristic peaks in the XRD diffraction spectrum of the sulfide solid electrolyte are located at 25.5±0.5°, 30.1±0.5°, and 31.5±0.5°.

3. The sulfide solid electrolyte according to claim 1, characterized in that The size of the sulfide electrolyte particles is 200nm-5μm, and the room temperature ionic conductivity is 6.0-12.0mS·cm -1 , the activation energy is 0.20-0.36 eV.

4. The method for preparing the sulfide solid electrolyte according to claim 1, characterized in that The following steps are involved: In an inert protective atmosphere and under anhydrous and oxygen-free conditions, the raw materials are dry-mixed according to the stoichiometric ratio of formula (I), then heat-treated at 400-600° C. for 3-30 hours, and finally cooled to obtain a sulfide electrolyte.

5. The method for preparing the sulfide solid electrolyte according to claim 4, characterized in that The rotation speed during dry mixing is 100-20000 rpm, preferably 10000-15000 rpm, and the dry mixing time is 3 minutes to 2 hours, preferably 5-10 minutes.

6. The method for preparing the sulfide solid electrolyte according to claim 4, characterized in that The heat treatment temperature is 480-550°C; the heat treatment time is 6-10 hours.

7. The method for preparing the sulfide solid electrolyte according to claim 4, characterized in that The raw material compound of the doping element M is a sulfide or a halide, and the raw material compound of the doping elements X and O is a lithium compound or a doping metal compound.

8. The method for preparing the sulfide solid electrolyte according to claim 4, characterized in that The raw material compound of the doping element M is a sulfide, and the raw material compound of the doping elements X and O is a lithium compound.

9. Application of the sulfide solid electrolyte according to claim 1 in all-solid-state batteries, characterized in that The method comprises pressing the sulfide solid electrolyte or a mixture thereof with a binder into a sheet, and then preparing a positive electrode, a negative electrode and a current collector on the upper and lower surfaces of the obtained electrolyte sheet respectively.

10. The use of the sulfide solid electrolyte in all-solid-state batteries as claimed in claim 9, characterized in that The mass percentage content of the sulfide solid electrolyte in the mixture of the sulfide solid electrolyte and the binder is not less than 80%; the binder is selected from at least one of polytetrafluoroethylene and polyamide.

Citation Information

Patent Citations

  • Sulfur oxide solid electrolyte, preparation method and application thereof

    CN111244534A

  • High-stability inorganic sulfide solid electrolyte and preparation method thereof

    CN113363569A

  • Inorganic sulfide solid electrolyte and preparation method thereof

    CN113471521A

  • Sulfide solid electrolyte and preparation method and application thereof

    CN115133116A

  • Vulcanized electrolyte and preparation method thereof, composition for composite electrolyte membrane, method for preparing composite electrolyte membrane, and lithium ion battery

    CN118289807A

Cited By

  • Multi-metal doped argyrodite type solid electrolyte, and preparation method and application thereof

    CN122051356A